Malignant hyperthermia (icarus syndrome): new view on the old problem - N. A. Shnayder; V. A. Shnayder (Нервно-мышечные болезни)
In the lecture shot history of research of etiology and pathogenesis of more dramatic complication of general anaesthesia – malignant hyperthermia - are presented. Importance of the interdisciplinary approach to working out of methods of preventive maintenance and treatment of it pharmacogenetics conditions in practice of the anaesthesiologist is underlined.